Electrodiagnosis in Lumbar Spinal Stenosis: A Review - GÜNDÜZ, OSMAN HAKAN (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2010)
Lumbar spinal stenosis (LSS) is a narrowing of the spinal canal and/or the neuroforamina through which the spinal cord roots enter and exit. The symptoms of LSS usually begin over the course of several months and include neurogenic claudication. This is characterized by low back pain that radiates down one or both legs producing pain or weakness. LSS can be quite debilitating and can have a profound negative effect on one's activities of daily living and overall quality of life. Imaging studies, such as computed tomography (CT) and magnetic resonance imaging (MRI) are routinely performed in the work-up of suspected LSS. In recent years, there has been much controversy over the actual clinical usefulness of these studies. When compared to electrodiagnostic studies, CT and MRI have been shown to have increased false negative and false positive rates. Electrodiagnostic studies show dynamic physiological neural function and has become a valuable tool in LSS. This information can be used to determine the location and severity of LSS, differentiate LSS from other conditions, and monitor the progression. Electrodiagnostic techniques such as somatosensory evoked potentials, dermatomal somatosensory evoked potentials (DSEPs), and paraspinal mapping (PM) increase both the sensitivity and specificity in diagnosing LSS. DSEPs provide useful information on multi-level, multiple rootlet disease. PM reflects the physiology of nerve roots and has been found to be superior to extremity needle EMG. Electrodiagnostic techniques are becoming the standard in the diagnosis and therapeutic decisions for LSS and other related diseases. Turk J Phys Med Rehab 2010;56:75-80.
Keywords: Lumbar spinal stenosis; electrodiagnosis; low back pain; lumbar radiculopathy; paraspinal mapping; SOMATOSENSORY-EVOKED-POTENTIALS; H-REFLEX AMPLITUDE; F-WAVE PARAMETERS; LOW-BACK-PAIN; LUMBOSACRAL RADICULOPATHY; ROOT COMPRESSION; PARASPINAL ELECTROMYOGRAPHY; AAEM MINIMONOGRAPH; TREADMILL TEST; DIAGNOSIS